Concept of knowledge in Ihya' 'Ulum al-Din Imam al-Ghazali's Perspective and Its Relevance to the Development of Islamic Economics - Moh. Faizin Faizin; Basuki Basuki (Jurnal Ushuluddin, 2026)
This research aims to analyze the concept of knowledge in the thought of Abu Hamid al-Ghazali in the bookIhya' 'Ulum al-Din. This study uses a qualitative approach with a library research method, namely by examining various relevant literature sources, especially primary texts.Ihya' 'Ulum al-Dinand scientific articles discussing al-Ghazali's thoughts and the development of Islamic economics. Data analysis was conducted using content analysis techniques to identify key themes related to the concept of knowledge in al-Ghazali's thought. The results of the study indicate that, first, al-Ghazali classifies knowledge into two main categories, namely fard 'ain knowledge and fard kifayah knowledge, which reflect the integration of religious and social dimensions in the development of knowledge. Second, al-Ghazali emphasizes the close relationship between knowledge and charity, where knowledge must be realized in concrete actions oriented towards moral values ​​and the benefit of the community. Third, the concept of knowledge in al-Ghazali's thought has strong relevance in the development of modern Islamic economics, particularly in building an economic system that is not only oriented towards efficiency, but also towards ethical values, justice, and social welfare. This study makes a scientific contribution by demonstrating that al-Ghazali's thought can serve as an epistemological foundation in the development of an integrative and benefit-oriented Islamic economic paradigm.